INDIKASI STRUKTUR SESAR DAN LIPATAN BAWAH PERMUKAAN DASAR LAUT PERAIRAN TUBAN, JAWA TIMUR - Prijantono Astjario (Jurnal Geologi dan Sumberdaya Mineral, 2007)
The marine geological and geophysical researches using a single channel seismic method in surrounding Turban water have been supported by echo sounder and marine sediment sampling activities. The single channel seismic record of 300 2 km has been made and it covers the area of about 1500 km . Those seismic profiling is perpendicular to the north coast of East Java with north - south direction and the cross line with east - west direction. The records are supposed to have a clear geological structure. Correlation of the geological structure based on the interpretation of seismic profiling of the sequence IV showed a similar east - west direction with the geological sequences of Rembang Basin. The sequence of sedimentary rocks of the Rembang Basin has been folded and faulted continuously from the land to the sea floor of the Java Sea.Â Keywords : seismic, echo sounder, geological structure, sequence, Rembang